Effectiveness participation of the nursing professional at the special education centers - Arias Fonseca, Dayana (2018)
Nursing in the school setting is a relatively new area in Costa Rica. The authorities in the country have drafted legislation and proposed strategies in health, childhood and rights that highlight the relevance of interventions that favor the health, education and development of children and adolescents with disabilities. This is how nursing care in the field of special education plays an important role in this population as well as in research. The objective is to analyze the best scientific evidence available regarding the effectiveness of educational participation and physical care by nursing students in special education centers to prevent health complications and promote the development of children with disabilities. It is a brief review protocol, using the methodology of clinical practice based on evidence, applying the five steps that are: 1. Approach of the clinical question 2. Search in databases 3. Critical analysis of the evidence 4. Transfer of evidence 5. Evaluation.